Role of product, market, and organisational characteristics on NPD benefits - García-Alcaraz, Jorge Luis (2018)
This paper reports a structural equation model for associate three Critical Success Factors (CSF) for New Product Development (NPD) as market, product and organisational characteristics (as independent variables) with benefits gained by customers and companies (as dependent variables). Eight premises were used for relationships among variables. The model is validated by using partial least squares techniques with information obtained from 197 product development managers in Mexican industry. Variables are validated by using Cronbach’s alpha, average variance extracted, R-squared and Variance Inflation Factor (VIF). Results indicate that six premises are accepted and two are rejected. According to findings, companies’ must define the market and product characteristics based on their technological and human resources skill available, aimed to take benefits to customer. The only way to gain benefits for the company is to guarantee the customer benefits, because relationship between these variables is statistically significant and not significant wet others.